Análise da expressão de genes para a sintase do casbeno em genótipos de pinhão manso com teor contrastante de ésteres de forbol - Nascimento, José Roberto da Silva (2017)
Jatropha curcas has a great economic potential due to its high oil and protein seeds content. However, the presence of toxic diterpenes, phorbol esters (PE), precludes the employment of the oil extraction residue into animal feed. PE biosynthesis has not yet been elucidated, casbene synthase is known to be involved in this biosynthetic pathway, and its product casbene is the most likely precursor to PE. In J. curcas, expression of none of the genes for caspase synthase has been found in seeds, but was reported to leaves and roots, the probable sites for PE synthesis. In order to evaluate the involvement of casbene synthase in regulation of PE biosynthesis and its accumulation, two genotypes with contrasting PE content were compared for the relative expression of casbene synthase genes in root and leaf. Nine genes were expressed in root and one was also expressed in leaf in both genotypes. The relative expression of casbene synthase in leaf was five times higher for the high PE content genotype, whereas in roots there was no significant difference for the relative expression between the genotypes. These results indicate that the leaves probably contribute significantly to PE biosynthesis and that the activity of casbene synthase in the regulation of phorbol esters biosynthesis is not determined transcriptionally. Additionally, we evaluated the efficiency of several protocols for in situ hybridization and in situ PCR in J. curcas aiming contribute to the development of in situ gene expression analysis techniques for this species. However, several obstacles were encountered to obtain satisfactory results. These techniques require a lot of time to be optimized as all adaptations must be empirically tested, which is very time and resource consuming and are often restricted to specific tissues and genes.